ChemInform Abstract: Chiral NCN Pincer Rhodium(III) Complexes with Bis(imidazolinyl)phenyl Ligands: Synthesis and Enantioselective Catalytic Alkynylation of Trifluoropyruvates with Terminal Alkynes. Issue 31 (11th July 2013) - Wang, Tao; Niu, Jun‐Long; Liu, Shuang‐Liang; Huang, Juan‐Juan; Gong, Jun‐Fang; Song, Mao‐Ping
Abstract The new chiral title catalyst can be applied to the synthesis of a wide range of different substituted and optically active propargylic alcohols.